PERANAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN PEMASARAN HASIL PERTANIAN DI KECAMATAN AJIBATA KABUPATEN TOBA SAMOSIR - Ompon Lastiur Sianipar; Asmawati Halilah Damanik (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
Indonesia is an agricultural country where most of the population earns a living from the agricultural sector. Until now, most of Indonesia's population uses natural resources to meet their needs and depend on the agricultural sector for their livelihood. High agricultural productivity will be in vain if it is not fully absorbed by the market. Various kinds of sales techniques that exist today can be directly sold in the market, through catalogs and what is currently developing is using the online method. Technology that is developing rapidly increases the rate of economic growth, unfortunately there are still many who have not taken advantage of technological advances, especially in the field of marketing agricultural products. The main source of income for the residents of Ajibata Subdistrict, Tobasa Regency, is from the agricultural sector and people's plantations. The agricultural products of Ajibata Regency are rice, corn, peanuts, cassava, sweet potato, coffee, cocoa, and candlenut. The results of this study indicate that Information Technology has a positive and significant effect in increasing the marketing of agricultural products in Ajibata District, Toba Samosir Regency. This is indicated by the tcount value of 5.418 which is greater than the t table value of 0.138 and the significance value of 0.000 which is smaller than the 0.05 significance value. So it can be concluded that Ha is accepted